PENGEMBANGAN USAHA BENIH JAGUNG TAHAN KERING - S.M. Sarwadana; B.R.T. Putri; K.K. Dinata (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Activities of science and technology for innovation and creativity campus aims are: (1) thecommercialization of science and technology campus creativity as a source of financing for the developmentof institutions; (2) stimulate the entrepreneurial spirit among beings campus, and (3) help people get seeds ofdrought-tolerant maize varieties. Methods of execution include the business aspects of the planned businessactivities consist of: provision of raw materials, production processes, management, marketing, humanresources, facilities, and financial. The raw material is obtained from units of science and technology fornovation and creativity campus and through partnerships with farmers' seed corn. The production processstarted from seed, sorting, and packaging. Marketing is done directly, partnerships with local governmentsand konsiniasi with kiosk / farm shop. Results show that the activities of science and technology unit forinnovation and creativity campus drought-tolerant maize seed has gone well characterized by supportinfrastructure adequate maize seed production; IbIKK unit operates under the management of PSAgroecotechnology Faculty of Agriculture, University of Udayana; Of investment made in 2014 amountingto Rp. 39,550,000; Result of sales corn seeds turnover in 2014 amounted to 400 kg (Rp. 12 million); and netcash flow amounted to 17,672,400.